Analyzing and Writing with Primary Sources - Conklin, Wendy (Professional Resources Ser., 2015)
Learn thought-provoking questions to help students deeply analyze primary sources to develop their close reading and writing skills. In each lesson, students respond to text-dependent questions, collaborate with others, and write in response to learning.